Catecolización de quitosano por dos rutas de síntesis con uso potencial para un adhesivo en medios húmedos (2017)
It has now been proven that catechol-containing molecules are capable of increasing the mucoadhesion of different polymers and have therefore been implemented in biomedical and biological fields such as wound dressings, hemostatic materials, and soft tissue supports. In the present work it is sought to enhance the properties of the mucoadhesion in a humid environment by the functionalization of chitosan using 3,4-dihydroxybenzaldehyde and pyrocatechol. Two different reactions were carried out, pyrocatechol-chitosan by Michael additionally and 3-4Dihydroxybenzaldehyde chitosan by Schiff base additionally. On the other hand, it is important to take into account that the% w / w ratios between catechol and chitosan differ between the two reactions as well as the reaction time and the aqueous medium in which they are made, thus showing the chemical changes at the end The reaction and quantity of products obtained, two products for 3,4-dihydroxybenzaldehyde and one for pyrocatechol. Finally, by means of a TGA, derived TGA and FTIR analysis, the effect of the chemical properties of each catecholization with respect to the pure reagents was identified. Functionalizations proved to be viable options for the future development of an adhesive in wet media.--Tomado del Formato de Documento de Grado.